A novel rapid synthesis of Fe2O3/graphene nanocomposite using ferrate(VI) and its application as a new kind of nanocomposite modified electrode as electrochemical sensor. (October 2015) - Karimi, Mohammad Ali; Banifatemeh, Fatemeh; Hatefi-Mehrjardi, Abdolhamid; Tavallali, Hossein; Eshaghia, Zarrin; Deilamy-Rad, Gohar
Graphical abstract: Highlights: A novel rapid synthesis of rGO–Fe2 O3 nanocomposite was developed using Fe(VI). Fe(VI) as an environmentally friendly oxidant was introduced for GO synthesis. Synthesized rGO–Fe2 O3 nanocomposite was applied as electrochemical sensor. A non-enzymatic sensor was developed for H2 O2 . Abstract: In this study, a novel, simple and sensitive non-enzymatic hydrogen peroxide electrochemical sensor was developed using reduced graphene oxide/Fe2 O3 nanocomposite modified glassy carbon electrode. This nanocomposite was synthesized by reaction of sodium ferrate with graphene in alkaline media. This reaction completed in 5 min and the products were stable and its deposition on the surface of electrode is investigated. It has been found the apparent charge transfer rate constant (ks) is 0.52 and transfer coefficient ( α ) is 0.61 for electron transfer between the modifier and glassy carbon electrode. Electrochemical behavior of this electrode and its ability to catalyze the electro-reduction of H2 O2 has been studied by cyclic voltammetry and chronoamperometry at different experimental conditions. The analytical parameters showed the good ability of electrode as a sensor for H2 O2 amperometric reduction.